Time, Digression and the Other (Side) in Juan Jose Saer's La grande - Lloyd Davies (Modern Language Review, 2020)
This essay focuses on the final novel, La grande (2005), of the Argentine writer, Juan José Saer (1937-2005) and focuses on his treatment of time in the light of the pressures posed by his impending death. It also analyses Saer’s disparagement of reason in a world governed by the pervasive influence of incoherence and discontinuity and his portraits of disability (both literal and metaphorical). Saer subordinates the intellect to the senses and literary rigour to freewheeling digressiveness. The conclusion considers the significance of the ‘lugar más grande’ that overshadows the ‘real’ world and ‘real’ time.